Excellent Aesthetics with Vital Bleaching and Porcelain Laminates Cooperation: A Case Report with 2 Years Follow Up - Emrullah Bahsi; Bayram Ince; Zehra Susgun Yildirim; Aydın Candan (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Objective: Dental bleaching offers a conservative, simplifi ed, and low cost approach to change the color of discolored teeth. The aim of this study is to present the restoration made with porcelain laminate veneers after vital bleaching. Case Report: A 24 years old male patient referred to Dicle University, Faculty of Dentistry, Department of Restorative Dentistry, because of the complaint of discolouration of teeth with laminate veneer preparation of anterior maxillary central teeth. For this patient, Philips Zoom was chosen. This material contains 25% hydrogen perioxide, which facilitates significant whitening procedure with a start to finish time of less than an hour. Optional curing light was used according to manufacturer's instructions, suction was performed using a surgical aspirator tip. After this treatment patient went to Prosthetic Dentistry clinic and porcelain laminate veneers were cemented. Conclusion: Vital tooth bleaching is an effective treatment modality that can significantly change the appearance of teeth. Sustainable multidisciplinary treatments is very effective in bringing the aesthetics and function.